Britain and the problem of international disarmament, 1919-1934 - Kitching, Carolyn, 1947- (Routledge studies in modern European history, 1999)
This study analyzes the disarmament policy of successive British governments from 1919 to 1934, concluding that the policy-makers' strategy was to avoid their international obligations for as long as possible.